Effects of QE on the asset prices in the US, EU and Japan - Borisova, Anastasiia; Sankot, Ondřej, 1988-; Šaroch, Stanislav, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This paper examines the process of implementation and transmission of quantitative easing policies, examines theoretical writings on the processes of how the quantitative easing program affects global and domestic financial markets, as well as macroeconomic indicators such as monetary base, consumer price index, the interest rate of one-year government bonds. Analyze and distinguish between conventional and unconventional monetary policy instruments within the historical evidence. The main research objective is to identify the effect of unconventional monetary policy on the assets price in the USA, EU, and Japan. The secondary objective of the thesis was to analyze the existing obstacles and risks of QE in the financial market. The masterwork used such methods as literature review, event study, statistical analysis, index DXY, modeling, analysis, synthesis, deduction, classification, systematic approach, and graphical method.
Vedoucí práce: Ondřej Sankot
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses